Corrosion-resistant industrial aluminum profile and manufacturing method thereof
通过对铝型材表面的脱脂、微蚀和阳极氧化处理,结合静电喷涂耐腐蚀涂料,解决了工业铝型材抗腐蚀性不足的问题,显著提高了其耐腐蚀性和耐水性,适用于户外环境。
Patent Information
- Application Number
- CN202411398439.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-09
AI Technical Summary
The existing industrial aluminum profiles have low corrosion resistance, especially in outdoor environments that are susceptible to ultraviolet rays and high temperatures, resulting in a degradation of coating performance and inability to effectively protect aluminum profiles, limiting their service life and application range.
By degreasing, micro-etching and anodizing the surface of the aluminum profile, a uniform oxide film is formed, and corrosion-resistant coating is sprayed using electrostatic spraying technology. The coating is based on epoxy resin and modified nano-silica and additives are added to improve the The bonding and wear resistance of the coating enhance the corrosion resistance and water resistance of the aluminum profile.
It significantly improves the corrosion resistance, water resistance and photoaging resistance of aluminum profiles, extends the service life, improves the heat resistance and wear resistance of the paint, and adapts to the working requirements of the outdoor environment.
Smart Images

Figure BDA0005074487570000041 
Figure BDA0005074487570000051 
Figure BDA0005074487570000052
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of aluminum profile preparation, and in particular relates to a corrosion-resistant industrial aluminum profile and a manufacturing method thereof. Background Art
[0002] With the increasing exhaustion of energy and the deterioration of the environment, governments around the world have increasingly higher requirements for energy conservation and emission reduction, resulting in more and more attention being paid to the field of new energy. In the field of new energy, solar energy is a green, pollution-free and inexhaustible energy. Compared with other energy sources, solar energy is universal in most areas of the earth and can be used locally. The use of solar energy is mainly through photovoltaic equipment using the photovoltaic effect to directly convert sunlight energy into electrical energy.
[0003] Commonly used photovoltaic equipment, especially solar panel frames, photovoltaic brackets, photovoltaic blocks, etc. are mostly industrial aluminum profiles. Industrial aluminum profiles are an alloy material with aluminum as the main component, which is made into aluminum materials of different cross-sectional shapes through hot melting and extrusion processes. It has many excellent properties, including light weight, high strength, good plasticity and processing performance, easy processing, beautiful appearance, non-magnetic, non-toxic, sound absorption and low temperature resistance. Although industrial aluminum profiles have excellent performance, their low corrosion resistance is low. The air contains CO2, SO2, H2S and other gases. When these polluting gases encounter water vapor in the air, they will produce micro-acids, which will corrode the aluminum profiles, causing the aluminum profiles to gradually lose their performance, greatly shortening the service life of the aluminum profiles, and seriously restricting their application.
[0004] At present, the common method to improve the corrosion resistance of industrial aluminum profiles is to spray paint on their surface to isolate the industrial aluminum profiles from the external environment and protect them. However, the existing corrosion-resistant protective coatings used for aluminum profiles are prone to peeling and falling off under the action of outdoor sun and rain, and have poor anti-ultraviolet performance. In addition, the temperature in summer is high, and under high temperature, the performance of the coating is seriously reduced, and it cannot play a protective role and cannot adapt to the working requirements of the outdoor environment. Therefore, it is urgent to solve the above problems to meet the higher demands in the field of aluminum profile preparation technology. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a corrosion-resistant industrial aluminum profile and a manufacturing method thereof.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for manufacturing a corrosion-resistant industrial aluminum profile comprises the following steps:
[0008] A1. After wiping the surface of the aluminum profile with acetone, immerse it in an aqueous solution of hexadecyltrimethylammonium bromide (mass fraction 2%) to degrease the surface to obtain a degreased aluminum profile;
[0009] A2. Spray micro-etching liquid on the surface of the degreased aluminum profile, wash and dry it, then put it into an oxidation tank for anodizing. After oxidation, wash it with water and dry it to obtain a pretreated aluminum profile;
[0010] A3. Electrostatic spraying is used on the surface of the pre-treated aluminum profile to spray corrosion-resistant paint. After spraying, it is sent to a curing box for curing. After curing is completed, it is naturally cooled to room temperature to obtain a corrosion-resistant industrial aluminum profile.
[0011] Furthermore, in step A2, the micro-etching solution is obtained by mixing hydrochloric acid, phosphoric acid, triethanolamine, diammonium hydrogen phosphate and water in a mass ratio of 1:1-4:1-3:2-4:30-40.
[0012] Furthermore, in step A3, during electrostatic spraying, the compressed air pressure is 0.5-0.7 MPa, the electrostatic spraying voltage is 40-60 KV, and the distance between the spray gun and the workpiece is 150-200 mm.
[0013] Furthermore, in step A3, the curing temperature is 200-220° C., and the curing time is 1-2 hours.
[0014] By degreasing and micro-etching the surface of the aluminum profile, the oxide film on the surface of the aluminum profile can be removed, and a microporous structure can be formed on the surface of the aluminum profile to improve the bonding strength of the spray layer during subsequent spraying; then, anodizing can produce an oxide film with a more uniform texture, thereby improving the corrosion resistance of the aluminum profile substrate; finally, electrostatic spraying can be used to obtain a smooth and uniform coating with a high utilization rate of the coating, saving costs.
[0015] Furthermore, the corrosion-resistant coating is prepared by the following steps:
[0016] B1. In a three-necked flask equipped with a stirring reflux device, bisphenol epoxy resin (epoxy value 0.54), ethylene glycol diglycidyl ether and an auxiliary agent were mixed, and 2-ethyl-4-methylimidazole (catalyst) was added. After stirring and mixing, nitrogen was introduced, and the reaction temperature was controlled to 140° C., and refluxed for 5 hours to obtain a modified epoxy resin;
[0017] B2. Put the modified epoxy resin, film-forming aid, curing accelerator and modified nano-silica prepared in step B1 into a ball mill and dry-mix for 10-15 hours, then pass through a 150-200 mesh sieve and obtain a corrosion-resistant coating by screening.
[0018] Furthermore, the raw materials are calculated in parts by weight as follows: 60-80 parts of bisphenol epoxy resin, 5-10 parts of ethylene glycol diglycidyl ether, 5-15 parts of auxiliary agent, 2-4 parts of 2-ethyl-4-methylimidazole, 1-3 parts of film-forming auxiliary agent, 0.5-1 parts of curing accelerator, and 8-16 parts of modified nano-silica.
[0019] Furthermore, the film-forming aid is one of dodecanoic acid ester, ethylene glycol monobutyl ether and polyethylene glycol octylphenyl ether.
[0020] Furthermore, the curing accelerator is one of 2-methylimidazole and 3-methylimidazole.
[0021] The prepared coating is based on epoxy resin, which gives the coating excellent corrosion resistance and water resistance. The curing accelerator can have a synergistic effect with the modified nano-silicon dioxide to jointly promote the curing of the epoxy resin.
[0022] Furthermore, the modified nano-silicon dioxide is prepared by the following steps:
[0023] The nano-silica was mixed with an ethanol aqueous solution, added to a magnetic stirring device, a magnet was added, stirring was started, and the mixture was dispersed for 15 minutes to uniformly disperse the nano-silica in the ethanol aqueous solution. The device was evacuated, N2 gas was introduced, and γ-aminopropyltriethoxysilane (silane coupling agent KH-550) was added. Oil bath heating was started and set to 50°C. Condensation water was turned on and the mixture was set to 80°C for reaction for 4 hours. The mixture was filtered, washed with ethanol, and dried in a vacuum drying oven for 2 hours to obtain modified nano-silica.
[0024] Furthermore, the usage ratio of the nano-silica, the ethanol aqueous solution, and γ-aminopropyltriethoxysilane is 1.0 g:100 mL:4.5 g.
[0025] There are many -OH groups on the surface of nano-silica, which can introduce -NH2 active groups by reacting with KH-550 to obtain modified nano-silica. Compared with ordinary nano-silica, it has better compatibility with the epoxy resin matrix and is easier to disperse. It can not only improve the wear resistance of the coating, but also act as a curing agent to promote the curing of the coating.
[0026] Furthermore, the auxiliary agent is prepared by the following steps:
[0027] S1. At room temperature, add mucic acid, DAST (diethylaminosulfur trifluoride, fluorination reagent) and dichloromethane into a flask, stir and mix evenly, react for 55 minutes, filter, take the filter cake, wash it with anhydrous ethanol for 3-4 times, and dry it to obtain intermediate 1; the ratio of mucic acid, DAST and dichloromethane is 20.9g:10.2g:100mL;
[0028] Under the action of the fluorination reagent, the hydroxyl group on the mucic acid is converted into a monofluorinated compound. The fluorination reagent is selective and the carboxyl group is not affected, thereby obtaining the intermediate 1. The specific reaction process is as follows:
[0029]
[0030] S2. In a three-necked flask equipped with a stirring reflux device, the intermediate 1, pentamethylpiperidinol and N,N-dimethylformamide (DMF) are mixed and stirred uniformly, and dicyclohexylcarbodiimide (DCC, dehydrating agent) and 4-dimethylaminopyridine (DMAP, catalyst) are added in sequence, and the reaction temperature is controlled to be 80° C. The reaction is carried out for 8 hours. After the reaction is completed, the mixture is filtered, and part of the solvent is removed by rotary evaporation. The mixture is washed 2-3 times and dried in vacuo to obtain the intermediate 2; the ratio of the amount of the intermediate 1, pentamethylpiperidinol, N,N-dimethylformamide, dicyclohexylcarbodiimide and 4-dimethylaminopyridine is 22.7 g:17.1 g:150 mL:20.6 g:0.2 g;
[0031] Under the action of DCC and DMAP, intermediate 1 and pentamethylpiperidinol undergo esterification reaction. By controlling the molar ratio of the two to be close to 1:1 and the intermediate 1 to be slightly excessive, only one carboxyl group on intermediate 1 participates in the reaction to obtain intermediate 2. The specific reaction process is as follows:
[0032]
[0033] S3. In a three-necked flask equipped with a stirring device, the intermediate 2, ethylenediamine and N,N-dimethylformamide were mixed and stirred evenly, dicyclohexylcarbodiimide was added, and the device was placed in a water bath, and the reaction was kept at 50°C for 4 hours. After the reaction was completed, it was filtered, most of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / petroleum ether, and the volume ratio of the two was 2:5), and the eluent was removed by rotary evaporation to obtain intermediate 3; the ratio of the amount of intermediate 2, ethylenediamine, N,N-dimethylformamide, and dicyclohexylcarbodiimide was 37.1g:7.3g:150mL:20.6g;
[0034] The carboxyl group on intermediate 2 and the amino group on ethylenediamine undergo an amidation reaction. Under the action of dicyclohexylcarbodiimide, the reaction can be carried out under relatively mild conditions. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of ethylenediamine, only one amino group on ethylenediamine participates in the reaction to obtain intermediate 3. The specific reaction process is as follows:
[0035]
[0036] S4. In a three-necked flask equipped with a stirring device, p-phenylene diisocyanate, intermediate 3 and dimethyl sulfoxide (DMSO) were mixed, tributyltin (catalyst) was added and mixed and stirred evenly, the temperature was gradually increased to 70°C, and the mixture was kept warm for 6 hours. Stirring was continued during the reaction. After the reaction was completed, the solvent was removed by vacuum distillation, and the mixture was dried in vacuo to obtain an auxiliary agent; the ratio of p-phenylene diisocyanate, intermediate 3, dimethyl sulfoxide and tributyltin was 18.4g:41.3g:150mL:2g;
[0037] The isocyanate group in p-phenylene diisocyanate reacts with the amino group on the intermediate 3 to generate a urea group. By controlling the molar ratio of the two to be close to 1:1 and a slight excess of p-phenylene diisocyanate, only one isocyanate group on p-phenylene diisocyanate participates in the reaction to obtain an auxiliary agent. The specific reaction process is as follows:
[0038]
[0039] The auxiliary agent molecule prepared by the present invention contains an isocyanate group at one end. The isocyanate group can react with the epoxy group in the epoxy resin matrix under the action of a catalyst to generate a five-membered oxazolidinone structure. Oxazolidinone is a five-membered heterocyclic ring. The introduction of oxazolidinone into the epoxy resin matrix can improve the strength and heat resistance of the epoxy resin matrix. In addition, the auxiliary agent is connected to the epoxy resin matrix through a chemical bond, which improves the migration resistance and exudation resistance of the auxiliary agent small molecule and improves the stability of the auxiliary agent. In addition, the auxiliary agent also contains a CF bond and a hindered phenol structure, wherein the CF bond has a small polarity and the CF bond has Very strong bond energy. The higher the chemical bond energy, the better the stability, which further improves the heat resistance and certain waterproof properties of the matrix. The fluorine atoms can be tightly arranged around the carbon atoms to form a protective barrier for the CC bonds, reducing the surface energy of the matrix and greatly enhancing the corrosion resistance of the matrix. Finally, the introduced hindered amine will decompose hydrogen dioxide to produce stable nitroxide free radicals. This compound can very effectively capture the free radicals produced in photooxidative degradation, effectively inhibit the photooxidative degradation of the matrix, and can be regenerated under stable conditions, thereby improving the anti-light aging properties of the epoxy resin matrix.
[0040] Beneficial effects of the present invention:
[0041] 1. The present invention can form a microporous structure on the surface of the aluminum profile by degreasing and micro-etching the surface of the aluminum profile, so as to improve the bonding force of the spray layer during subsequent spraying;
[0042] 2. Anodizing produces a more uniform oxide film, which can improve the corrosion resistance of the aluminum profile substrate;
[0043] 3. Electrostatically spray corrosion-resistant coating on the surface of aluminum profiles. The coating is based on epoxy resin, which isolates the aluminum profiles from the external environment and improves the corrosion resistance and water resistance of the aluminum profiles.
[0044] 4. Compared with ordinary nano-silicon dioxide, the prepared nano-silicon dioxide has better compatibility with the epoxy resin matrix, can improve the wear resistance of the coating, and can also promote the curing of the coating;
[0045] 5. The prepared additive can significantly enhance the heat resistance, corrosion resistance, light aging resistance and water resistance of the coating to a certain extent, and the performance is long-lasting and stable;
[0046] Therefore, the aluminum profile prepared by the present invention has excellent corrosion resistance and water resistance, and the coating sprayed on the surface of the aluminum profile has good wear resistance, stable and efficient corrosion resistance, heat resistance and light aging resistance, and has important application value in the field of aluminum profile preparation technology. DETAILED DESCRIPTION
[0047] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] Embodiment 1
[0049] Preparation aids:
[0050] S1. At room temperature, add 20.9 g of mucic acid, 10.2 g of DAST and 100 mL of dichloromethane into a flask, stir and mix evenly, react for 55 min, filter, take the filter cake, wash it with anhydrous ethanol for 4 times, and dry it to obtain intermediate 1;
[0051] S2. In a three-necked flask equipped with a stirring reflux device, 22.7 g of intermediate 1, 17.1 g of pentamethylpiperidinol and N,N-dimethylformamide were mixed and stirred evenly, and 20.6 g of dicyclohexylcarbodiimide and 0.2 g of 4-dimethylaminopyridine were added in sequence. The reaction temperature was controlled to 80 ° C. The reaction was carried out for 8 hours. After the reaction was completed, the reaction was filtered, and part of the solvent was removed by rotary evaporation. The mixture was washed 3 times and vacuum dried to obtain intermediate 2.
[0052] S3, in a three-necked flask equipped with a stirring device, 37.1g of intermediate 2, 7.3g of ethylenediamine and 150mL of N,N-dimethylformamide were mixed and stirred evenly, 20.6g of dicyclohexylcarbodiimide was added, the device was placed in a water bath, and the reaction was kept at 50°C for 4h. After the reaction was completed, it was filtered, most of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / petroleum ether, and the volume ratio of the two was 2:5), and the eluent was removed by rotary evaporation to obtain intermediate 3;
[0053] S4. In a three-necked flask equipped with a stirring device, 18.4 g of p-phenylene diisocyanate, 41.3 g of intermediate 3 and 150 mL of dimethyl sulfoxide were mixed, 2 g of tributyltin was added and the mixture was stirred evenly, the temperature was gradually increased to 70°C, and the mixture was kept warm for 6 hours with continuous stirring during the reaction. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was dried in vacuo to obtain an auxiliary agent.
[0054] Embodiment 2
[0055] Preparation aids:
[0056] S1. At room temperature, 41.8 g of mucic acid, 20.4 g of DAST and 200 mL of dichloromethane were added to a flask and stirred to mix evenly. The mixture was reacted for 55 min, and then filtered. The filter cake was taken, washed with anhydrous ethanol for 4 times, and dried to obtain intermediate 1.
[0057] S2. In a three-necked flask equipped with a stirring reflux device, 45.4 g of intermediate 1, 34.2 g of pentamethylpiperidinol and N,N-dimethylformamide were mixed and stirred evenly, and 41.2 g of dicyclohexylcarbodiimide and 0.4 g of 4-dimethylaminopyridine were added in sequence. The reaction temperature was controlled to 80 ° C. The reaction was carried out for 8 hours. After the reaction was completed, the reaction was filtered, and part of the solvent was removed by rotary evaporation. The mixture was washed 3 times and vacuum dried to obtain intermediate 2.
[0058] S3, in a three-necked flask equipped with a stirring device, 74.2g of intermediate 2, 14.6g of ethylenediamine and 300mL of N,N-dimethylformamide were mixed and stirred evenly, 41.2g of dicyclohexylcarbodiimide was added, the device was placed in a water bath, and the reaction was kept at 50°C for 4h. After the reaction was completed, it was filtered, most of the solvent was removed by rotary evaporation, and then purified by column chromatography (the eluent was a mixed solvent of ethyl acetate / petroleum ether, and the volume ratio of the two was 2:5), and the eluent was removed by rotary evaporation to obtain intermediate 3;
[0059] S4. In a three-necked flask equipped with a stirring device, 36.8 g of p-phenylene diisocyanate, 82.6 g of intermediate 3 and 300 mL of dimethyl sulfoxide were mixed, 4 g of tributyltin was added and the mixture was stirred evenly, the temperature was gradually increased to 70°C, and the reaction was kept warm for 6 hours with continuous stirring during the reaction. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and the mixture was dried in vacuo to obtain an auxiliary agent.
[0060] Embodiment 3
[0061] Preparation of modified nano-silica:
[0062] Mix 1.0 g of nano-silica with 100 mL of ethanol-water solution, add to a magnetic stirring device, add a magnet, start stirring, and disperse for 15 minutes to evenly disperse the nano-silica in the ethanol-water solution. Evacuate the device, introduce N2 gas, add 4.5 g of γ-aminopropyltriethoxysilane, start oil bath heating, set to 50°C, turn on condensation water, set to 80°C for reaction for 4 hours, filter, wash with ethanol, and then dry in a vacuum drying oven for 2 hours to obtain modified nano-silica.
[0063] Embodiment 4
[0064] Preparation of corrosion resistant coatings:
[0065] B1. In a three-necked flask equipped with a stirring reflux device, 60 g of bisphenol epoxy resin (epoxy value 0.54), 5 g of ethylene glycol diglycidyl ether and 5 g of the auxiliary agent prepared in Example 1 were mixed, and then 2 g of 2-ethyl-4-methylimidazole was added. After stirring and mixing, nitrogen was introduced, the reaction temperature was controlled to 140 ° C, and refluxed for 5 hours to obtain a modified epoxy resin;
[0066] B2. Put the modified epoxy resin obtained in step B1, 1 g of ethylene glycol monobutyl ether, 0.5 g of 2-methylimidazole, and 8 g of the modified nano-silicon dioxide obtained in Example 3 into a ball mill and dry-mix them for 10 hours. Then, pass through a 150-mesh sieve and obtain a corrosion-resistant coating by screening.
[0067] Embodiment 5
[0068] Preparation of corrosion resistant coatings:
[0069] B1. In a three-necked flask equipped with a stirring reflux device, 70 g of bisphenol epoxy resin (epoxy value 0.54), 8 g of ethylene glycol diglycidyl ether and 10 g of the auxiliary agent prepared in Example 2 were mixed, and 3 g of 2-ethyl-4-methylimidazole was added. After stirring and mixing, nitrogen was introduced, the reaction temperature was controlled to 140 ° C, and refluxed for 5 hours to obtain a modified epoxy resin;
[0070] B2. Put the modified epoxy resin obtained in step B1, 2 g of polyethylene glycol octylphenyl ether, 0.1 g of 3-methylimidazole, and 12 g of modified nano-silicon dioxide obtained in Example 3 into a ball mill and dry-mix them for 15 hours. Then, pass through a 200-mesh sieve and obtain a corrosion-resistant coating by screening.
[0071] Embodiment 6
[0072] Preparation of corrosion resistant coatings:
[0073] B1. In a three-necked flask equipped with a stirring reflux device, 80 g of bisphenol epoxy resin (epoxy value 0.54), 10 g of ethylene glycol diglycidyl ether and 15 g of the auxiliary agent prepared in Example 2 were mixed, and then 4 g of 2-ethyl-4-methylimidazole was added. After stirring and mixing, nitrogen was introduced, the reaction temperature was controlled to 140 ° C, and refluxed for 5 hours to obtain a modified epoxy resin;
[0074] B2. Put the modified epoxy resin prepared in step B1, 3 g of dodecanoic acid ester, 1 g of 3-methylimidazole, and 16 g of modified nano-silicon dioxide prepared in Example 3 into a ball mill and dry-mix them for 15 hours. Then, pass through a 200-mesh sieve and obtain a corrosion-resistant coating by screening.
[0075] Embodiment 7
[0076] A1. After wiping the surface of the aluminum profile with acetone, immerse it in an aqueous solution of hexadecyltrimethylammonium bromide (mass fraction 2%) to degrease the surface to obtain a degreased aluminum profile;
[0077] A2. Spray micro-etching liquid on the surface of the degreased aluminum profile, wash and dry it, then put it into an oxidation tank for anodizing. After oxidation, wash it with water and dry it to obtain a pretreated aluminum profile;
[0078] A3. Electrostatic spraying was used on the surface of the pretreated aluminum profile to spray the corrosion-resistant coating prepared in Example 5. During spraying, the compressed air pressure was 0.5 MPa, the electrostatic spraying voltage was 40 KV, and the distance between the spray gun and the workpiece was 150 mm. After spraying, the aluminum profile was sent to a curing box for curing at a curing temperature of 200 ° C. The curing time was 1 h. After curing was completed, the aluminum profile was naturally cooled to room temperature to obtain a corrosion-resistant industrial aluminum profile.
[0079] The micro-etching solution is obtained by mixing hydrochloric acid, phosphoric acid, triethanolamine, diammonium hydrogen phosphate and water in a mass ratio of 1:1:1:2:30.
[0080] Embodiment 8
[0081] A1. After wiping the surface of the aluminum profile with acetone, immerse it in an aqueous solution of hexadecyltrimethylammonium bromide (mass fraction 2%) to degrease the surface to obtain a degreased aluminum profile;
[0082] A2. Spray micro-etching liquid on the surface of the degreased aluminum profile, wash and dry it, then put it into an oxidation tank for anodizing. After oxidation, wash it with water and dry it to obtain a pretreated aluminum profile;
[0083] A3. Electrostatic spraying was used on the surface of the pretreated aluminum profile to spray the corrosion-resistant coating prepared in Example 6. During spraying, the compressed air pressure was 0.7 MPa, the electrostatic spraying voltage was 60 KV, and the distance between the spray gun and the workpiece was 200 mm. After spraying, the aluminum profile was sent to a curing box for curing at a curing temperature of 220° C. for 2 h. After curing was completed, the aluminum profile was naturally cooled to room temperature to obtain a corrosion-resistant industrial aluminum profile.
[0084] The micro-etching solution is obtained by mixing hydrochloric acid, phosphoric acid, triethanolamine, diammonium hydrogen phosphate and water in a mass ratio of 1:4:3:4:40.
[0085] Comparative Example 1
[0086] No additives were added and the remaining steps were the same as those in Example 6 to prepare the coating.
[0087] Comparative Example 2
[0088] Use commercially available corrosion resistant paint.
[0089] The following performance tests were performed on Examples 4, 5 and 6 and Comparative Examples 1 and 2 according to different test standards:
[0090] The national standard GB / T 9286-2021 "Scratch test method for paints and varnishes" is used to measure the adhesion of the sample before and after standing at 180°C for 12 hours;
[0091] The national standard GB / T 1732-2020 "Determination of impact resistance of paint film" is used to measure the impact resistance;
[0092] The water resistance is determined by the immersion test method according to the national standard GB / T 1733-1993 "Determination of water resistance of paint film";
[0093] The light aging resistance is tested according to the national standard GB / T 1865-2009 and rated according to the GB / T 1766 standard;
[0094] The wear resistance is measured using the national standard GB / T 23988-2009 "Falling sand method for determination of wear resistance of coatings";
[0095] The national standard GB / T 1763 "Determination of chemical resistance of paint film" is used to determine the acid and alkali resistance;
[0096] The salt spray resistance is measured using the national standard GB / T1771-1991 "Determination of neutral salt spray resistance of paints and varnishes";
[0097]
[0098]
[0099] It can be seen from the above table that the coating prepared in the embodiment of the present invention has good wear resistance, and also has stable and efficient corrosion resistance, heat resistance and light aging resistance. Spraying it on the surface of aluminum profiles can improve various properties of the aluminum profiles. Therefore, the present invention has important application value in the field of aluminum profile preparation technology.
[0100] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0101] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for manufacturing a corrosion-resistant industrial aluminum profile, characterized in that: The following steps are involved: A1. After wiping the surface of the aluminum profile with acetone, immerse it in an aqueous solution of hexadecyltrimethylammonium bromide to degrease the surface to obtain a degreased aluminum profile; A2. Spray micro-etching liquid on the surface of the degreased aluminum profile, wash and dry it, then put it into an oxidation tank for anodizing. After oxidation, wash it with water and dry it to obtain a pretreated aluminum profile; A3. Electrostatic spraying is used on the surface of the pre-treated aluminum profile to spray corrosion-resistant paint. After spraying, curing is carried out. After curing is completed, cooling is performed to obtain a corrosion-resistant industrial aluminum profile.
2. The method for manufacturing a corrosion-resistant industrial aluminum profile according to claim 1, characterized in that: The corrosion-resistant coating in step A3 is prepared by the following steps: B1, bisphenol epoxy resin, ethylene glycol diglycidyl ether and an auxiliary agent are mixed, and then 2-ethyl-4-methylimidazole is added, stirred and mixed, nitrogen is introduced, and refluxed at 140° C. for 5 hours to obtain a modified epoxy resin; B2. Put the modified epoxy resin, film-forming aid, curing accelerator and modified nano-silica prepared in step B1 into a ball mill for dry mixing, sieve and obtain the corrosion-resistant coating through sieving.
3. The method for manufacturing a corrosion-resistant industrial aluminum profile according to claim 2, characterized in that: The auxiliary agent is prepared by the following steps: S1. At room temperature, add mucic acid, DAST and dichloromethane into a flask, stir and mix evenly, react for 55 minutes, filter, take the filter cake, wash and dry to obtain intermediate 1; S2, mixing intermediate 1, pentamethylpiperidinol and N,N-dimethylformamide and stirring evenly, adding dicyclohexylcarbodiimide and 4-dimethylaminopyridine in sequence, reacting at 80°C for 8h, filtering, rotary evaporating, washing, and vacuum drying to obtain intermediate 2; S3, mixing intermediate 2, ethylenediamine and N,N-dimethylformamide, adding dicyclohexylcarbodiimide, reacting at 50°C for 4h, filtering, rotary evaporation, column chromatography purification, and rotary evaporation to obtain intermediate 3; S4. Mix p-phenylene diisocyanate, intermediate 3 and dimethyl sulfoxide, add tributyltin and mix well, keep warm at 70°C for 6 hours, stir continuously during the reaction, and after the reaction is completed, distill under reduced pressure and dry to obtain an auxiliary agent.
4. The method for manufacturing a corrosion-resistant industrial aluminum profile according to claim 3, characterized in that: The ratio of the amount of mucic acid, DAST and dichloromethane used in step S1 is 20.9 g:10.2 g:100 mL.
5. The method for manufacturing a corrosion-resistant industrial aluminum profile according to claim 3, characterized in that: In step S2, the ratio of the amount of intermediate 1, pentamethylpiperidinol, N,N-dimethylformamide, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 22.7 g: 17.1 g: 150 mL: 20.6 g: 0.2 g.
6. The method for manufacturing a corrosion-resistant industrial aluminum profile according to claim 3, characterized in that: In step S3, the ratio of the amount of intermediate 2, ethylenediamine, N,N-dimethylformamide, and dicyclohexylcarbodiimide is 37.1 g:7.3 g:150 mL:20.6 g.
7. The method for manufacturing a corrosion-resistant industrial aluminum profile according to claim 3, characterized in that: In step S4, the ratio of the amount of p-phenylene diisocyanate, intermediate 3, dimethyl sulfoxide and tributyltin is 18.4 g:41.3 g:150 mL:2 g.
8. The method for manufacturing a corrosion-resistant industrial aluminum profile according to claim 2, characterized in that: The raw materials of the corrosion-resistant coating are calculated in parts by weight as follows: 60-80 parts of bisphenol epoxy resin, 5-10 parts of ethylene glycol diglycidyl ether, 5-15 parts of additives, 2-4 parts of 2-ethyl-4-methylimidazole, 1-3 parts of film-forming additives, 0.5-1 parts of curing accelerators, and 8-16 parts of modified nano-silicon dioxide.
9. The method for manufacturing a corrosion-resistant industrial aluminum profile according to claim 1, characterized in that: In step A2, the micro-etching solution is prepared by mixing hydrochloric acid, phosphoric acid, triethanolamine, diammonium hydrogen phosphate and water in a mass ratio of 1:1-4:1-3:2-4:30-40.
10. A corrosion-resistant industrial aluminum profile, characterized in that: Prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Processing technology of aluminum profile with high corrosion resistance
CN114262922A
Polyurea modified epoxy resin anticorrosive paint and preparation method thereof
CN117343612A
Heat-insulating glass containing functional coating and manufacturing method of heat-insulating glass
CN118146691A
Epoxy-based solvent-free anticorrosive paint as well as preparation method and use method thereof
CN118562365A
Cited By
Corrosion-resistant aluminum profile machining process
CN120326293A